Genomic analyses reveal distinct genetic architectures and selective pressures in buffaloes. Issue 2 (21st February 2020) - Sun, Ting; Shen, Jiafei; Achilli, Alessandro; Chen, Ningbo; Chen, Qiuming; Dang, Ruihua; Zheng, Zhuqing; Zhang, Hucai; Zhang, Xiaoming; Wang, Shaoqiang; Zhang, Tao; Lu, Hongzhao; et al.
Abstract: Background: The domestic buffalo ( Bubalus bubalis ) is an essential farm animal in tropical and subtropical regions, whose genomic diversity is yet to be fully discovered. Results: In this study, we describe the demographic events and selective pressures of buffalo by analyzing 121 whole genomes (98 newly reported) from 25 swamp and river buffalo breeds. Both uniparental and biparental markers were investigated to provide the final scenario. The ancestors of swamp and river buffalo diverged ∼0.23 million years ago and then experienced independent demographic histories. They were domesticated in different regions, the swamp buffalo at the border between southwest China and southeast Asia, while the river buffalo in south Asia. The domestic stocks migrated to other regions and further differentiated, as testified by (at least) 2 ancestral components identified in each subspecies. Different signals of selective pressures were also detected in these 2 types of buffalo. The swamp buffalo, historically used as a draft animal, shows selection signatures in genes associated with the nervous system, while in river dairy breeds, genes under selection are related to heat stress and immunity. Conclusions: Our findings substantially expand the catalogue of genetic variants in buffalo and reveal new insights into the evolutionary history and distinct selective pressures in river and swamp buffalo.